A peculiar orthodoxy : reflections on theology and the arts - Begbie, Jeremy (Grand Rapids, MI : Baker Academic, 2018)
World-renowned theologian Jeremy Begbie has been at the forefront of teaching and writing on theology and the arts for more than twenty years. Amid current debates and discussions on the topic, Begbie emphasizes the role of a biblically grounded creedal orthodoxy as he shows how Christian theology and the arts can enrich each other. Throughout the book, Begbie demonstrates the power of classic trinitarian faith to bring illumination, surprise, and delight whenever it engages with the arts
World-renowned theologian Jeremy Begbie has been at the forefront of teaching and writing on theology and the arts for more than twenty years. Amid current debates and discussions on the topic, Begbie emphasizes the role of a biblically grounded creedal orthodoxy as he shows how Christian theology and the arts can enrich each other. Throughout the book, Begbie demonstrates the power of classic trinitarian faith to bring illumination, surprise, and delight whenever it engages with the arts.
Includes bibliographical references and index
Keywords: Christianity and the arts